PENGARUH PEMBERIAN JUICE KACANG HIJAU TERHADAP PENINGKATAN PRODUKSI ASI IBU NIFAS - Handayani, Saadah (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2023)
Introduction: Mother's Milk (ASI) is the single most perfect food for babies in the first 6 months of growth, without any additional drinks or food. The low level of exclusive breastfeeding is caused by problems that are often caused by breastfeeding mothers, namely milk production that is not optimal. One of the factors that can affect milk production is the nutrition of breastfeeding mothers. Phaseolus radiatus is a food ingredient that can stimulate milk production. Objective: to determine the effect of giving green bean juice on milk production in postpartum mothers. Methods: This research is a quantitative research with a quasi-experimental method with a one group pretest posttest research design. The population of postpartum mothers at the Kebondalem Health Center, Pemalang Regency, with a total of 30 postpartum mothers using accidental sampling technique, totaled 16 samples of postpartum mothers. Data analysis used the Wilcoxon test with a ? value of 0.005 or asym.sig <0.05. Results: the average postpartum mother has doubled her milk production before and after consuming green bean juice regularly for 3 days.Conclusion: There is an effect of giving green bean juice to increase milk production in postpartum mothers.